Alteration in liver function tests among patients hospitalized for COVID-19: a multicentric study in Peru - Marín-Dueñas, Ivania (2021)
Introduction: COVID-19 affects the liver, causing alteration in liver biochemistry tests such as aspartate transferase (AST), alanine transferase (ALT), alkaline phosphatase (ALP), total bilirubin and albumin. Objective: To determine the prevalence of alteration in liver functions tests and associated factors for severity among Peruvian COVID-19 patients. Materials and methods: A descriptive, retrospective and cross-sectional study was performed in 4 public hospitals in Peru. Patients admitted to hospitalization wards and intensive care units with a diagnosis COVID-19 were enrolled. The evaluation of AST, ALT, ALP, total bilirubin and albumin was performed. Associations with demographic and medical data were assessed. Results: 1,100 patients were enrolled, of which 81.7% had altered liver function tests. Only 2.8% of the patients had cirrhosis and 2.1% hepatitis B/C virus. AST and ALT were altered at admission in 64.7% and 63.7%, of the patients respectively. Factors associated with liver injury were: being female OR=0.53 (95% CI: 0.39-0.73; p<0.01), dyslipidemia OR=1.72 (95% CI: 1.10-2.70; p=0.01), previous medication OR=1.56 (95% CI: 1.12 -2.16, p<0.01) and fever OR=1.43 (95% CI: 1.03-1.199, p=0.03). Disease severity was associated with levels of AST and ALT (p<0.01). Patients taking self-medication OR=1.56 (95% CI: 1.12-2.16; p<0.01) and paracetamol OR= 1.41 (95% CI:1.01-1.98; p=0.04) had higher risk of liver injury. Meanwhile, corticosteroids OR=0.55 (95% CI: 0.38-0.78; p<0.01) and enoxaparin OR=0.53 (95% CI: 0.35- 0.81; p<0.01) were protective factors. Conclusions: Peruvian patients with COVID- teration in liver function tests, high levels of AST and ALT were related to disease severity.